KAJIAN KETERLAMBATAN KEDATANGAN KERETA API PENUMPANG TERHADAP KINERJA OPERASI DAERAH OPERASI 1 JAKARTA - Masjraul Hidayat; Djayo Anggoro; Iqbal Firdaus (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of the research is to analyze the effect of the delay arrival of railway to the operational performance of the first regional in Jakarta. To solve the problem, the research used some methods; unstructured data collecting, library research, and companies’ data. While for the data analysis used simple linear regression, basic counting of railway delay arrival and operational performance. The results show that there is an effect of the railway delay arrival (X) as 38.44 to the operational performance of the first regional (Y) with the interpretation of coefficient correlation as 0.62. The results mean that the effect is strong enough.